Role of human resources in the tourism industry with special reference to Jammu and Kashmir - Ganie, Showkat Ahmad; Ahmad Dar, Muzaffar (Turizam, 2020)
Abstract: Tourism, nowadays is one of the most preferred and popular ways of spending leisure time. The natural urge and appetite of every human being for gaining new experiences and eagerness to get entertained and educated are the main drivers of tourism. It is one of the largest and fastest-growing economic activities, directly concerned with generating services, products, employment, and investments. It is a dynamic and competitive industry and constantly needs to adapt to the changing needs and desires of its customers. Tourism being a service industry is largely driven by its human resources, wherein they play a very crucial role in its growth and development. It is such a resource of an organization that appreciates and advances with time and supports the organization in executing its policies, strategies, and programmes. Tourists visit a particular destination because of its inherent natural or cultural value, historical significance, natural beauty, offering leisure, adventure, and amusement and all such things, as a gift of nature can’t be found at one place in the whole world, but in the state of Jammu and Kashmir(J&K), known for its scenic beauty and fascinating climate. Tourism is one of the most fascinating industries of the J&K economy wherein the role of its human resources is quite promising and of utmost importance for its growth and development. This paper is an endeavor to highlight the role and significance of human resources in the growth and development of the tourism industry and the role they play in promoting tourism with special reference to J&K state.